Implementation of State Administrative Court Decisions: Conception, and Barriers - Imron Rizki A; Rizki Mustika Suhartono; Safrin Salam (Musamus Law Review, 2021)
This research aims to analyze how the effectiveness of the implementation of the ruling of the Administrative Court of the State and what are the factors that influence the effectiveness of the Court ruling The country. The research was carried out on the courts of The State of Makassar, data collection techniques are carried out by means of interviews and read scientific books, magazines, newspapers and other readings related to research. Results of the study showed that the effectiveness of the implementation of the ruling of the Court of The Country has not been effective, because so far there are still many Administrative Bodies and Officials of countries that are unwilling to comply with the ruling of the Court of The country, then plus the lack of participation of the parties to the dispute has led to a court could not ascertain whether a State Administrative Court ruling that has a magnitude of law has been implemented or not. As for the factors that influence the Court ruling The Country, among which is the absence of a special eksekutorial institution or institution of sanctions in carrying out the Court ruling The country, The official low awareness Countries in obeying the Court ruling The Country, the absence of more detailed provisions governing sanctions if the verdict is not implemented. Advice from the research is that, should the Government contains provisions governing the institutions eksekutorial institutions or special sanctions ruling of The judiciary of the State, so the State Administrative Court's verdict can be run and judicial administration can emerge again in the eyes of the community.